Rationality and Salience (Aporia, 2017)
One would hope that you know when your father's birthday is. What was the status of this knowledge five minutes ago, when presumably your father's birthday was not at the forefront of your mind? Five minutes ago your belief of the form "My father's birthday is on the _ of the month" was insalient. This paper explores the ways in which rationality is affected by the fact that our beliefs can be more or less salient at any given time. I will advance two main theses- the first, which I will call the 'weak' thesis, says that two scenarios can remain constant with respect to the beliefs that an agent has, vary with respect to which beliefs are salient, and vary with respect to what is rational. Roughly speaking, the weak thesis says that salience matters to rationality. I then argue for a particular conception of how salience matters to rationality, which I will call the 'strong' thesis. The strong thesis says that given facts about which beliefs are salient, one is irrational only insofar as one has inconsistencies in one's salient beliefs. I intend the strong thesis to be useful for someone attempting to give a formalisation of rationality which takes salience into account.